The unique features of Greek cities as catalysts for implementing a polycentric city model for urban sustainability - Christoforaki, Katerina (Technical Annals, 2025)
Greek cities exhibit unique characteristics that can serve as catalysts for implementing the polycentric city model as a means to enhance urban sustainability. This paper explores how Greece’s urban structure, historical development, and land-use patterns create both challenges and opportunities in adopting this model. While Greek cities inherently possess mixed-use neighborhoods, which align with the core principles of polycentricity, persistent urban issues such as inefficient mobility networks, fragmented governance, and limited public participation hinder progress. The study examines global case studies, particularly the 15-minute city model implemented in Paris, and assesses its applicability within the Greek context. Key factors, including mobility strategies, land-use policies, and citizen engagement, are analyzed to determine their feasibility in Greek cities. Furthermore, the research highlights the importance of fostering local adaptation rather than direct replication of international models. Findings indicate that while Greece has a comparative advantage in certain aspects of polycentric urbanism, targeted interventions are required to address existing urban shortcomings. These include strengthening sustainable mobility infrastructures, preserving the diversity of urban functions, and fostering public participation in planning processes. Ultimately, the study advocates for a strategic, context-specific approach to integrating polycentric principles into Greek urban environments, ensuring resilience, sustainability, and improved quality of life for residents.